Timing of Postoperative CSF Leak after Endoscopic Skull Base Surgery in Patients with Obstructive Sleep Apnea - Zimmermann, Terence M.; Marcellino, Chris R.; Choby, Garret W.; Gompel, Jamie J. Van; O'Brien, Erin K.; Abel, Katie M. Van; Janus, Jeffrey R.; Link, Michael J.; Frank, Ryan D.; Stokken, Janalee K. (Journal of Neurological Surgery Part B: Skull Base, 2019)
Background There is little data regarding postoperative outcomes of patients with obstructive sleep apnea (OSA) undergoing skull base surgery. The purpose of this study is to determine an association between risk factors and proximity of cerebrospinal fluid (CSF) leak to surgery in patients with OSA undergoing endoscopic skull base surgery.Methods A retrospective review of neurosurgical inpatients, with and without OSA, at a tertiary care institution from 2002 to 2015 that experienced a postoperative CSF leak after undergoing endoscopic skull base surgery.Results Forty patients met inclusion criteria, 12 (30%) with OSA. OSA patients had significantly higher body mass index (BMI; median 39.4 vs. 31.7, p < 0.01) and were more likely to have diabetes (41.7 vs. 10.7%, p = 0.04) than non-OSA patients; otherwise there were no significant differences in clinical comorbidities. No patients restarted positive pressure ventilation (PPV) in the inpatient setting. The type of repair was not a significant predictor of the time from surgery to leak. Patients with OSA experienced postoperative CSF leak 49% sooner than non-OSA patients (Hazard Ratio 1.49, median 2 vs. 6 days, log-rank p = 0.20).Conclusion Patients with OSA trended toward leaking earlier than those without OSA, and no OSA patients repaired with a nasoseptal flap (NSF) had a leak after postoperative day 5. Due to a small sample size this trend did not reach significance. Future studies will help to determine the appropriate timing for restarting PPV in this high risk population. This is important given PPV's significant benefit to the patient's overall health and its ability to lower intracranial pressure.
Keywords: cerebrospinal fluid leak; obstructive sleep apnea; endoscopic skull base surgery; obesity